A DEMATEL Integrated Interval Valued Intuitionistic Fuzzy PROMETHEE Approach for Parking Lots Evaluation - (:unkn) unknown (OLD CITY PUBLISHING INC, 2018)
High population density of Istanbul results with the scarcity of parking spaces. Authorities are planning to construct various parking lots in Istanbul to satisfy increasing car park requirement. To find convenient locations and construct well-designed parking lots, current ones should be evaluated firstly. In this study, a special version of parking lots, Park&Ride (P&R) facilities, are studied considering the need to support public transport usage. Randomly chosen P&R lots in Istanbul are compared according to the literature based criteria by using interval-valued intuitionistic fuzzy Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE). However, the number of evaluation criteria for P&R lots are large and firstly some of them are eliminated by using Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique. The case study verifies the effectiveness of the proposed methodology. Also, results are analyzed for different importance degrees of criteria.
Keywords: Parking lots; park&ride; public transportation; DEMATEL; interval valued intuitionistic fuzzy sets; PROMETHEE; DECISION-MAKING APPROACH; RIDE; SELECTION; SETS; CRITERIA; INFORMATION; EXTENSION; STATIONS; SERVICE; TOPSIS